Implementation of an Automatic Defacement Detection System on Government Websites Using N8N - Faisal Anwar; Apriade Voutama (Prodi Sistem Informasi Universitas Dharma Andalas, 2026)
Advances in information technology have encouraged the use of websites as a means of public services in various sectors. One sector that utilizes websites to support its services is the government sector. However, in its implementation, this system faces cybersecurity challenges, namely defacement attacks, which involve unauthorized changes to the appearance or content of a website that are often detected too late and can erode public trust. This research aims to develop a system capable of detecting indications of defacement attacks automatically and more quickly. The method applied in this research is a system experiment approach, which utilizes the n8n workflow automation platform, operated on a scheduled basis via schedule triggers. This system is tasked with monitoring website domains by applying analytical techniques based on keyword matching to page content that is potentially subject to change. The monitoring data is then processed using a function node to match specific keywords, such as